Effect of distance between grooves on the wear of structured grinding wheels - Costa, Sharlane Maria (2021)
During roughing and surface finishing operations a lot of heat is generated in the grinding wheel/workpiece contact zone. The surface structuring/texturing of abrasive wheels has been a proposal to reduce the operating temperature. In this work, three spiral grooved abrasive discs were produced, with different distances between grooves. The wear behavior of structured grinding wheels was evaluated by lubricated pin-on-disc tests. Results show that the inclusion of grooves, and the reduction of the distance between them, allows a more efficient lubrication of pin/disc contact zone, reducing the temperature in this zone while wear debris are eliminated, thus modifying the wear conditions.